Stabilitas Loci? - Vogeler, Georg (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2024)
"Virtual archives of religious orders using the example of Monasterium.net" - Digitisation has added a virtual location to the physical ‘archive’, where the written records of an institution are kept. The European document portal ‘Monasterium.net’, which is the largest of its kind with over 600,000 items from 14 European countries, has established itself as such a virtual location. Religious archives share with the portal that the institution of the ‘religious community’ can also do without a geographically fixed location. Although centrally organised religious orders have established their own administration at the geographical headquarters, the self-image as a community of religious makes the religious community at least multi-local. Monasterium.net, as a database that can be organised both according to established archive structures and as an aggregation of selected documents, is a possible location for this and the archives of the Teutonic Order have also attempted to realise this to some extent. However, the document database also offers the potential to rethink ‘virtual archives of religious orders’: a portal such as Monasterium.net offers various methods to represent the historical identity of a religious order: aggregating archival collections created in single institutions and form new collections by content referencing the religious order. The paper illustrates the AI based methods about to be implemented in Monasterium.net that support deeper study of the content of the documents. These methods are used in the ‘Be-CoRe’ project, which analyses selected Cistercian and Benedictine monasteries in France and Austria in the late Middle Ages. In the virtual archive of a religious order created by these methods, we can find hints towards the importance of the regional context of the monasteries compared to supra-regional references.